Perovskite pure-phase microcrystalline material and preparation method and application thereof
Through the combination of good solvent A and anti-solvents B and C, the problem of difficult to obtain pure phases in the preparation of perovskite microcrystalline materials is solved, and perovskite microcrystals with high purity and single crystal phase are achieved, thereby improving pertitanium Efficiency of mine solar cells.
Patent Information
- Application Number
- CN202310761879.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2024-12-27
AI Technical Summary
In existing perovskite solar cells, it is difficult to obtain pure phase materials for the preparation of perovskite microcrystalline materials, resulting in problems of impurities and low efficiency. In particular, the phase separation of multi-component/widebandgap materials seriously affects device efficiency. .
The combination method of good solvent A and anti-solvents B and C is used to form a precursor liquid by dissolving the raw materials, and the perovskite microcrystals precipitate and phase change through slow dropping addition and heating, and clean with anti-solvent C to obtain pure phase perovskite. Microcrystals ensure high purity and single crystal phase of perovskite microcrystals.
The high purity of perovskite microcrystals (up to more than 90%) is achieved, and the phase separation defect is avoided. The obtained perovskite microcrystals are suitable for the growth of perovskite films and improve the efficiency of solar cells.
Smart Images

Figure CN119194613A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor materials, and in particular to a perovskite pure phase microcrystalline material and a preparation method and application thereof. Background Art
[0002] Solar cells are devices that directly convert light energy into electrical energy through the photoelectric effect or photochemical effect. Perovskite solar cells (PSC) are solar cells that use perovskite-type organic metal halide semiconductors as light-absorbing materials. Currently, the efficiency of perovskite solar cells has reached 25.7%, exceeding that of traditional polycrystalline silicon solar cells.
[0003] In the mass production process of perovskite solar cells, there are problems such as high prices for high-purity materials and low yields caused by chemical measurement errors in the preparation process of the precursor solution. Studies have pointed out that pre-synthesized perovskite microcrystals can be used as raw materials for the preparation of precursor solutions, which can solve the above problems to a certain extent. However, it is difficult to obtain pure-phase perovskite microcrystals using existing methods for preparing pre-synthesized perovskite microcrystals. For example, dry microcrystal preparation methods such as ball milling are not only difficult to remove impurities from raw materials, but also easily cause phase separation; while existing wet microcrystal synthesis technology is mostly used for single-component / narrow-bandgap perovskite materials, but the products are prone to certain impurities such as solvent intermediate phases, and the purity is not high, which is especially difficult to apply to multi-component / wide-bandgap perovskite materials. This is because multi-component / wide-bandgap perovskite materials will also have more serious phase separation, which seriously affects the efficiency of devices based on these perovskite microcrystal materials. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a pure-phase perovskite microcrystalline material, so as to improve the problem of low purity of the pure-phase perovskite microcrystalline material prepared in the prior art.
[0005] Another object of the present invention is to provide a perovskite pure phase microcrystalline material.
[0006] Another object of the present invention is to provide applications of perovskite pure phase microcrystalline materials.
[0007] In a first aspect, an embodiment of the present invention provides a method for preparing a perovskite pure phase microcrystalline material, comprising:
[0008] Providing raw materials for forming perovskite, including a cationic compound for providing cations and an anionic compound for providing anions;
[0009] Dissolving the raw material using good solvent A to form a precursor solution;
[0010] Using antisolvent B to precipitate perovskite microcrystals;
[0011] Using antisolvent B to phase-transform the perovskite microcrystals;
[0012] Using anti-solvent C to wash the perovskite microcrystals to obtain pure phase perovskite microcrystal materials;
[0013] The solubility of the good solvent A for the whole raw material of the perovskite is not less than 0.4 mol / L, but the solubility of the good solvent A for some or all components in the raw material is not higher than 0.1 mol / L.
[0014] Optionally, the proton number (Gutmann Donor number) of the good solvent A is not higher than 20.
[0015] Optionally, the good solvent A is a polar solvent, selected from at least one of ether solvents, lactone solvents, and organic acid lipid solvents.
[0016] Optionally, the good solvent A is selected from at least one of ethylene glycol methyl ether, γ-butyrolactone, δ-valerolactone, ε-caprolactone, propylene carbonate, and diethyl succinate.
[0017] Optionally, any two of the good solvent A, the anti-solvent B and the anti-solvent C need to be miscible in any proportion.
[0018] Optionally, the anti-solvent B has a solubility of no more than 0.1 mol / L for each component in the raw material; the anti-solvent B has a solubility of no more than 0.1 mol / L for the perovskite microcrystals; and / or
[0019] The solubility of the anti-solvent C for each component in the raw material is no higher than 0.1 mol / L; the solubility of the anti-solvent C for the perovskite microcrystals is no higher than 0.1 mol / L.
[0020] Optionally, the boiling point of the anti-solvent B is 140-165° C.; and / or
[0021] The boiling point of the anti-solvent C is 40-80°C.
[0022] Optionally, the anti-solvent B is a non-polar or low-polar solvent selected from benzene solvents, ether solvents, and ester solvents with the number of carbon atoms on the carbon chain being not less than 4.
[0023] Optionally, the anti-solvent B is selected from at least one of anisole, o-xylene and butyl propionate; and / or
[0024] The anti-solvent C is selected from at least one of diethyl ether, toluene, cyclopentane, ethyl acetate and methyl acetate.
[0025] Optionally, in the precursor solution, the overall concentration of the perovskite is not less than 0.4 mol / L.
[0026] Optionally, the volume ratio of the good solvent A, anti-solvent B and anti-solvent C is 1:(3-20):(1-3).
[0027] Optionally, using anti-solvent B to precipitate perovskite microcrystals comprises:
[0028] Slowly drop the precursor solution into the anti-solvent B, stir, and let stand to obtain a precipitate;
[0029] The addition rate of the precursor solution is 0.03-0.2 mL / s; and the stirring rate is 500-2000 rad / min.
[0030] Optionally, using anti-solvent B to phase-transform the perovskite microcrystals comprises:
[0031] The perovskite microcrystals and anti-solvent B are mixed, heated at a temperature not higher than the boiling point of the anti-solvent B for 30 to 180 minutes, cooled, and allowed to stand to obtain a pure phase perovskite microcrystal precipitate.
[0032] The heating temperature is not less than 130°C.
[0033] Optionally, the perovskite microcrystals are cleaned with an anti-solvent C to obtain a pure phase perovskite microcrystal material, including:
[0034] The pure phase perovskite microcrystals that have undergone phase change are precipitated, washed 3-5 times with anti-solvent C, filtered, and vacuum dried to obtain pure phase perovskite microcrystals.
[0035] Optionally, the cationic compound is selected from the group consisting of + , Rb + , K + 、Na + At least one compound selected from the group consisting of + 、MA + DMA + , MDA + At least one compound of
[0036] The anionic compound is selected from the group consisting of - Br - , Cl - HCOO - 、SCN - 、BF4 - PF6 - At least one compound.
[0037] Optionally, the raw materials include lead iodide, formamidine iodine, lead bromide, cesium iodide, lead chloride, and methylamine chloride;
[0038] The good solvent A has a solubility of no more than 0.1 mol / L for the lead iodide, lead bromide, cesium iodide, lead chloride and methylamine chloride.
[0039] In a second aspect, the present application further provides a perovskite pure phase microcrystalline material, which is prepared by the preparation method described in the first aspect.
[0040] Optionally, the particle size of the perovskite pure phase microcrystalline material is 0.5 to 2 μm.
[0041] In the third aspect, the present application also provides the calcium
[0042] Application of the perovskite pure phase microcrystalline material prepared by the preparation method of the perovskite pure phase microcrystalline material or the perovskite pure phase microcrystalline material described in the second aspect in the fields of X-ray detection, solar cells, and photoelectric detection.
[0043] The present application embodiment provides a method for preparing a pure phase perovskite microcrystalline material, which uses a good solvent A with cluster solubility to dissolve the raw materials used to prepare the perovskite to form a precursor solution, and the precursor solution formed by the good solvent A is treated in sequence by anti-solvent B and anti-solvent C, so that the perovskite microcrystals are precipitated and phase-transformed into pure α-phase perovskite microcrystals. Among them, when the raw material good solvent A dissolves the single raw material components separately, its solubility is low, but the solubility of the perovskite microcrystal clusters formed by each raw material is high, so that when the raw material of the perovskite microcrystal is dissolved in the good solvent A, the raw material exists in the solution in the form of clusters with a fixed stoichiometric ratio to exclude excess raw materials and insoluble impurities, so that the obtained perovskite microcrystals have higher purity and fewer impurities. At the same time, since the good solvent A has a low proton number and poor ability to form coordination with the raw materials, it is difficult to form a stable intermediate phase, which helps to eliminate the intermediate phase residue in the perovskite microcrystal product and realize the purification of the perovskite microcrystal. For wide bandgap perovskite microcrystals, various cations and anions are prone to phase separation during the formation of perovskite microcrystals due to differences in their solubility, which leads to mixed crystals. This preparation method utilizes the cluster solubility of the good solvent A to mix the crystal phase in the precursor solution in advance, avoiding the phase separation defect during the microcrystal formation process, so that the wide bandgap perovskite microcrystals obtained not only have low impurity content but also have no other crystal phases, and obtain pure α-phase wide bandgap perovskite microcrystals. The perovskite microcrystals obtained by this preparation method have high purity, a yield of up to 90%, a single crystal phase, and a relatively simple process flow, which is easy to promote and utilize.
[0044] The embodiment of the present application also provides a perovskite pure phase microcrystalline material, which is a pure phase microcrystalline material of a single α crystal phase, has no other crystal phases, has high purity, and low impurity content, and is conducive to the growth and preparation of perovskite thin films. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a SEM image of product A obtained in Example 1 of the method for preparing a pure-phase perovskite microcrystalline material provided in the present application;
[0046] Figure 2 The XRD spectrum of the product A obtained in Example 1 of the method for preparing the pure phase microcrystalline perovskite material provided in the present application;
[0047] Figure 3 This is a SEM image of product B obtained in Example 2 of the method for preparing a pure-phase perovskite microcrystalline material provided in the present application;
[0048] Figure 4 The XRD spectrum of the product B obtained in Example 2 of the method for preparing the pure phase microcrystalline perovskite material provided in the present application;
[0049] Figure 5 This is a SEM image of product C obtained in Example 3 of the method for preparing a pure-phase perovskite microcrystalline material provided in the present application;
[0050] Figure 6 The XRD spectrum of the product C obtained in Example 3 of the method for preparing the pure phase microcrystalline perovskite material provided in the present application;
[0051] Figure 7 This is a SEM image of the product D obtained in Example 4 of the method for preparing the pure phase microcrystalline perovskite material provided in the present application;
[0052] Figure 8 The XRD spectrum of the product D obtained in Example 4 of the method for preparing the pure phase microcrystalline perovskite material provided in the present application;
[0053] Fig. 9 This is a SEM image of the product E obtained in Example 5 of the method for preparing the pure phase microcrystalline perovskite material provided in the present application;
[0054] Fig.10 The XRD spectrum of the product E obtained in Example 5 of the method for preparing the pure phase microcrystalline perovskite material provided in the present application;
[0055] Fig.11 This is a SEM image of comparative product A obtained in comparative example 1 in the method for preparing the pure phase microcrystalline perovskite material provided in the present application;
[0056] Fig.12The XRD spectrum of the comparative product A obtained in Comparative Example 1 in the preparation method of the pure phase microcrystalline perovskite material provided in the present application;
[0057] Fig.13 This is a SEM image of comparative product B obtained in comparative example 2 in the method for preparing the pure phase microcrystalline material of perovskite provided in the present application;
[0058] Fig.14 The XRD spectrum of the comparative product B obtained in Comparative Example 2 in the method for preparing the pure phase microcrystalline material of perovskite provided in the present application;
[0059] Fig.15 This is a SEM image of comparative product C obtained in comparative example 3 in the method for preparing the pure phase microcrystalline material of perovskite provided in the present application;
[0060] Fig.16 The XRD spectrum of the comparative product C obtained in Comparative Example 3 in the method for preparing the pure phase microcrystalline perovskite material provided in the present application;
[0061] Fig.17 This is a SEM image of comparative product D obtained in Comparative Example 4 in the method for preparing the pure phase microcrystalline material of perovskite provided in the present application;
[0062] Fig.18 The XRD spectrum of the comparative product D obtained in Comparative Example 4 in the preparation method of the pure phase microcrystalline material of perovskite provided in the present application;
[0063] Fig.19 This is a SEM image of comparative product E obtained in comparative example 5 in the method for preparing the pure phase microcrystalline material of perovskite provided in the present application;
[0064] Fig. 20 The XRD spectrum of the comparative product E obtained in Comparative Example 5 in the preparation method of the pure phase microcrystalline material of perovskite provided in the present application;
[0065] Fig.21 This is a SEM image of comparative product F obtained in Comparative Example 6 in the method for preparing the pure phase microcrystalline material of perovskite provided in the present application;
[0066] Fig. 22 This is the XRD spectrum of the comparative product F obtained in Comparative Example 6 in the method for preparing the pure phase microcrystalline perovskite material provided in the present application.
[0067] Abbreviations and key terms used in this description
[0068] Cluster dissolution
[0069] In this application, "cluster" should be understood as a relatively stable microscopic or submicroscopic aggregate composed of several or even thousands of atoms, molecules or ions through physical or chemical binding forces. Therefore, in this application, cluster dissolution should be understood as: the dissolution process of microscopic or submicroscopic aggregates formed by molecules or ions corresponding to perovskite microcrystals formed by raw materials in solution in the solvent.
[0070] Proton number of the solvent (Gutmann Donor number)
[0071] In the present application, "the proton number of a solvent (Gutmann Donor number)" should be understood as a quantitative description of the performance of a Lewis base in a Lewis acid-base system; it means the number of positive charges that a solvent can provide when the solvent, which acts as a Lewis base, forms a stable or unstable coordination compound with an anion or cation of a solute during the dissolution process. DETAILED DESCRIPTION
[0072] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0073] The present application provides a method for preparing a pure-phase perovskite microcrystalline material, comprising:
[0074] Providing raw materials for forming perovskite, including a cationic compound for providing cations and an anionic compound for providing anions;
[0075] Dissolving the raw material using good solvent A to form a precursor solution;
[0076] The precursor solution is added dropwise into anti-solvent B to precipitate perovskite microcrystals;
[0077] Using antisolvent B to phase-transform the perovskite microcrystals;
[0078] Using anti-solvent C to wash the perovskite microcrystals to obtain pure phase perovskite microcrystal materials;
[0079] The solubility of the good solvent A for the whole raw material of the perovskite is not less than 0.4 mol / L, but the solubility of the good solvent A for some or all components in the raw material is not higher than 0.1 mol / L.
[0080] It should be noted that "the solubility of good solvent A for some or all of the components in the raw material" should be understood as: the solubility when good solvent A is used to dissolve some or all of the components in the raw material. It should be noted that "the solubility of the good solvent A for the raw material of the perovskite as a whole is not less than 0.4 mol / L" should be understood as: the solubility of good solvent A for the raw material as a whole when all the components contained in the raw material are added to good solvent A together.
[0081] It should be noted that in the present application, "the separate solubility of the good solvent A for some components in the raw material" should be understood as: when the components of the raw material include FAI and / or MAI, the separate solubility of the good solvent A for the remaining components in the raw material except FAI and MAI; when the components in the raw material do not include FAI and MAI, the separate solubility of the good solvent A for any component in the raw material.
[0082] In the prior art, when using raw materials to form perovskite microcrystals, the solvent used is usually a solvent with good solubility in the raw materials, such as dimethyl sulfoxide (DMSO) and dimethylformamide (DMF), to ensure the solubility of the raw materials. However, solvents with good solubility in the raw materials, such as DMSO or DMF, are easy to form relatively stable intermediate complexes with the raw materials during the process of dissolving the raw materials, making it difficult to be removed during the precipitation process, and are easy to precipitate together with the perovskite microcrystals, resulting in a high impurity content and low purity of the perovskite microcrystals, resulting in the introduction of impurities into the precursor solution used to prepare the perovskite film, which is not conducive to the formation of the perovskite film. For wide bandgap or multi-component perovskite materials, the above-mentioned solvents with good solubility in the raw materials are also easy to cause phase separation, resulting in the perovskite microcrystal product containing a mixture of multiple phases, which has a greater impact on solar cell devices.
[0083] Based on this technical problem, the inventors proposed the use of a good solvent and two anti-solvents to form pure phase perovskite microcrystals, so that the obtained perovskite microcrystals are not only of high purity, with a yield of more than 90%; and for wide bandgap / multi-component perovskite microcrystals, pure phase, α phase, wide bandgap / multi-component perovskite microcrystals can be obtained, which improves the phase separation defect of wide bandgap / multi-component perovskite microcrystals using existing dry microcrystal preparation technology or wet microcrystal synthesis technology, provides pure phase, high-purity microcrystal raw materials for perovskite films, which is beneficial to the efficiency of devices based on perovskite films.
[0084] In the present application, although the good solvent A is a good solvent for perovskite microcrystals or wide bandgap / multi-component perovskite microcrystals, its solubility for a single raw material should not be too high. It can even be that while its solubility for single-component perovskite microcrystals or wide bandgap / multi-component perovskite microcrystals is sufficient, its solubility for a single raw material is lower and better, which is beneficial to the removal of impurities in the formed perovskite microcrystals and avoiding phase separation of wide bandgap / multi-component perovskite microcrystals.
[0085] In some embodiments, the ability of the good solvent A to provide protons in the solution is no more than 20, that is, the good solvent A is a solvent with a proton number no more than 20, preferably no more than 19. The good solvent is preferably a solvent with a low proton providing ability, which is beneficial for it not to form a stable solvent intermediate with the raw material, but to form an unstable solvent intermediate phase, which is beneficial to the formation of high-purity, pure-phase perovskite microcrystals.
[0086] Furthermore, the good solvent A is a polar solvent, which can be selected from at least one of ether solvents, lactone solvents, and organic acid lipid solvents. It should be noted that "good solvent A is a polar solvent" in this application should be understood as the polarity of good solvent A is strong, at least its polarity should be higher than that of anti-solvent B and anti-solvent C. Exemplarily, the good solvent A can be selected from at least one of ethylene glycol methyl ether, γ-butyrolactone, δ-valerolactone, ε-caprolactone, propylene carbonate, and diethyl succinate; preferably, the good solvent A is a single solvent, that is, it is selected from any one of ethylene glycol methyl ether, γ-butyrolactone, δ-valerolactone, ε-caprolactone, propylene carbonate, and diethyl succinate, which is more conducive to the purification of perovskite microcrystals and avoids phase separation. Among them, the good solvent A listed here is only an exemplary good solvent A, and it can also use other solvents that meet the above-mentioned solubility conditions and / or proton number conditions and polarity conditions.
[0087] In some embodiments, the anti-solvent B is a non-polar or low-polarity solvent, which can be selected from at least one of a benzene solvent, an ether solvent, and an ester solvent with a carbon chain having no less than 4 carbon atoms. Exemplarily, the anti-solvent B can be selected from at least one of anisole, o-xylene, and butyl propionate. It should be noted that the polarity of the anti-solvent B of the present application should be at least lower than the polarity of the good solvent A. Preferably, the anti-solvent B is a single solvent, that is, it is selected from any one of anisole, o-xylene, and butyl propionate, which is more conducive to the purification of perovskite microcrystals and avoids phase separation.
[0088] In some embodiments, the anti-solvent B should be selected from solvents having a solubility of no more than 0.1 mol / L for each component in the raw material and a solubility of no more than 0.1 mol / L for the perovskite microcrystals. The anti-solvent B listed here is only an exemplary anti-solvent B, and other solvents that meet the above solubility conditions and polarity conditions may also be used.
[0089] In some embodiments, the anti-solvent C is a non-polar or low-polarity solvent, and its solubility for each component in the raw material is not higher than 0.1 mol / L and its solubility for the perovskite microcrystals is not higher than 0.1 mol / L. Exemplarily, it can be selected from at least one of ether, toluene, cyclopentane, ethyl acetate, and methyl acetate. Preferably, the anti-solvent C is a single solvent, that is, it is selected from any one of ether, toluene, cyclopentane, ethyl acetate, and methyl acetate, which is more conducive to the purification of perovskite microcrystals and avoids phase separation.
[0090] In some embodiments, any two of the good solvent A, anti-solvent B and anti-solvent C need to be miscible in any proportion; that is, any two of the good solvent A, anti-solvent B and anti-solvent C, or all three of them can be miscible in any proportion, which is beneficial to the full removal of impurities in the perovskite microcrystals and the transformation to other phases (phases other than the α phase).
[0091] In some embodiments, the boiling point of the anti-solvent B is 140-160°C, which is conducive to the phase transformation of wide bandgap / multi-component perovskite microcrystals. Because wide bandgap / multi-component perovskite microcrystals are prone to different phases during the precipitation process, such as α-phase perovskite microcrystals and δ-phase perovskite microcrystals, and δ-phase perovskite microcrystals can be converted into α-phase perovskite microcrystals at a certain temperature. Therefore, the boiling point of anti-solvent B should not be lower than the temperature at which perovskite microcrystals of other phases are converted into α-phase perovskite microcrystals, which is conducive to the phase transformation of perovskite microcrystals.
[0092] In some embodiments, in the precursor solution, the overall concentration of perovskite is not less than 0.4 mol / L, preferably not less than 0.45 mol / L, and more preferably 0.5 mol / L. This is because the higher the overall concentration of perovskite, the more conducive it is to the precipitation of microcrystals, and at the same time, it can greatly reduce the use of various solvents and reduce production costs; it should be noted that in this application: "overall concentration of perovskite" should be understood as the concentration of the amount of perovskite that can be theoretically formed by the raw materials used in the system.
[0093] Furthermore, the volume ratio of the good solvent A, anti-solvent B and anti-solvent C is 1:(3-20):(1-3). This is because when the volume of good solvent A is fixed at 1, in the crystallization stage, a sufficiently high ratio of anti-solvent B is required to cooperate with it so that the perovskite microcrystals are completely precipitated; under the premise of satisfying the complete precipitation of perovskite microcrystals, the amount of anti-solvent B can be reduced as much as possible to save materials. In the stage of cleaning the microcrystals, a sufficiently high ratio of anti-solvent C is required to clean out the anti-solvent B remaining in the microcrystals; under the condition of satisfying complete cleaning, the amount can be reduced as much as possible to save materials. This ratio needs to be adjusted according to the different choices of good solvent A, anti-solvent B and anti-solvent C.
[0094] In some embodiments, using anti-solvent B to precipitate perovskite crystals comprises:
[0095] Slowly drop the precursor solution into the anti-solvent B, stir, and let stand to obtain a precipitate;
[0096] The addition rate of the precursor solution is 0.03-0.2 mL / s; the stirring speed is 500-2000 rad / min. Preferably, the addition rate of the antisolvent B is 0.04-0.05 mL / s; the stirring speed is 1000-1500 rad / min. The addition rate of the precursor solution should not be too high or too low, because a too high addition rate leads to incomplete crystallization, while a too low addition rate leads to a too long reaction time, and the crystallites agglomerate, which affects the subsequent phase change process.
[0097] In some embodiments, using antisolvent B to phase-transform the perovskite microcrystals comprises:
[0098] The perovskite microcrystals and anti-solvent B are mixed, heated at a temperature not higher than the boiling point of the anti-solvent B for 30-180 minutes, cooled, and allowed to stand to obtain a pure phase perovskite microcrystal precipitate.
[0099] The heating temperature is preferably a temperature close to the boiling point of the antisolvent B but not equal to the boiling point of the antisolvent B, which is conducive to the conversion of perovskite crystallites of other phases into perovskite crystallites of α phase.
[0100] In some embodiments, the perovskite microcrystals are cleaned with anti-solvent C to obtain a pure phase perovskite microcrystal material, comprising:
[0101] The pure phase perovskite microcrystals after phase change are precipitated, washed 3-5 times with anti-solvent C, filtered, and vacuum dried to obtain pure phase perovskite microcrystals. The boiling point of the anti-solvent C is 40-80° C. Preferably, the lower the boiling point of the anti-solvent C, the more conducive it is to shorten the drying process.
[0102] In the present application, the cationic compound includes at least one inorganic cationic compound and at least one organic cationic compound; the anionic compound includes at least one anionic compound. When the pure phase perovskite microcrystal to be prepared is a single-component perovskite microcrystal, its inorganic cationic compound is one,
[0103] Optionally, the cationic compound includes at least one inorganic cationic compound and at least one organic cationic compound; and the anionic compound includes at least one anionic compound.
[0104] Optionally, the inorganic cationic compound is selected from + , Rb + , K + 、Na + At least one compound of
[0105] The organic cationic compound is selected from the group consisting of + 、MA + DMA + , MDA + At least one compound of
[0106] The anionic compound is selected from the group consisting of - Br - , Cl - HCOO - 、SCN - 、BF4 - PF6 - At least one compound.
[0107] Optionally, the raw materials are selected from at least one of cesium iodide, rubidium iodide, potassium iodide, sodium iodide, cesium bromide, rubidium bromide, potassium bromide, sodium bromide, cesium chloride, rubidium chloride, potassium chloride, and sodium chloride, and at least one selected from formamidine iodine, formamidine bromide, formamidine bromide, methylamine chloride, methylamine iodine, methylamine bromide, dimethylammonium iodine, dimethylammonium bromide, dimethylammonium chloride, methylenediammonium iodine, methylenediammonium bromide, and methylenediammonium chloride, and at least one selected from lead iodide, lead chloride, and lead bromide.
[0108] Preferably, the preparation method provided in the present application is particularly suitable for multi-component perovskite pure phase microcrystalline materials. Therefore, the organic cationic compounds, inorganic cationic compounds, and anionic compounds in the raw materials can be selected from a variety of sources. For example, the components of the raw materials described in the present application can be lead iodide, formamidine iodine, lead bromide, cesium iodide, lead chloride, and methylamine chloride.
[0109] The perovskite pure phase microcrystalline material provided in the present application can be used not only to prepare perovskite pure phase microcrystalline materials with lead as inorganic cation, but also to prepare perovskite pure phase microcrystalline materials based on other inorganic cations, such as Cs + It can not only be used to prepare I — The pure phase microcrystalline material of perovskite as anion can also be used to prepare Br-based — , Cl — The pure phase microcrystalline perovskite material with anions such as Cs has a wide range of applications, which overcomes the narrow application range of the pure phase microcrystalline perovskite material in the current prior art and is difficult to be applied to Cs + Inorganic cations or Br — , Cl — In a second aspect, the present application also provides a perovskite pure phase microcrystalline material, wherein the perovskite pure phase microcrystalline material is an α-phase perovskite microcrystalline.
[0110] In the present application, “the perovskite pure phase microcrystalline material is an α-phase perovskite microcrystalline” should be understood as the content of the α-phase perovskite microcrystalline in the perovskite pure phase microcrystalline material obtained in the present application infinitely approaches 100%, and the content of the perovskite microcrystalline of the other phases infinitely approaches 0%, which can be specifically manifested as the characteristic peaks of the perovskite microcrystalline of the other phases are difficult to detect or negligible compared to the intensity of the characteristic peaks of the corresponding α-phase perovskite microcrystals when analyzed by X-ray diffraction. In addition, the content of impurities in the perovskite pure phase microcrystalline material also infinitely approaches 0%, which can be specifically manifested as the characteristic peaks of the impurities are difficult to detect or negligible compared to the intensity of the characteristic peaks of the corresponding α-phase perovskite microcrystals when analyzed by X-ray diffraction.
[0111] In some embodiments, the perovskite pure phase microcrystalline material provided in the present application can be a single-component / narrow bandgap perovskite microcrystalline material, or a multi-component / wide bandgap perovskite pure phase microcrystalline material, and the crystal phase of the perovskite microcrystalline is a single α phase.
[0112] The molecular formula of any perovskite microcrystal included in the perovskite pure phase microcrystalline material is ABX3; illustratively, A corresponding to each perovskite microcrystal is independently selected from any one or more of FA (formamidine), MA (methylamine), DMA (dimethylammonium), and MDA (methylenediammonium); B corresponding to each perovskite microcrystal is independently selected from any one or more of Pb and Sn; X corresponding to each perovskite microcrystal is - Independently selected from I — (iodide ion), Br — (bromide ion), Cl — (Chloride ion), HCOO — (Carboxylate), SCN— (Thiocyanate), BF4 — (boron tetrafluoride), PF6 — (phosphorus hexafluoride).
[0113] In some embodiments, the perovskite pure phase microcrystalline material is prepared by the preparation method described in the first aspect, and the particle size of the perovskite pure phase microcrystalline material is 0.5 to 2 μm.
[0114] In a third aspect, the present application also provides the application of the perovskite pure phase microcrystalline material prepared by the preparation method of the perovskite pure phase microcrystalline material described in the first aspect or the perovskite pure phase microcrystalline material described in the second aspect in the fields of X-ray detection, solar cells, and photoelectric detection.
[0115] Among them, the solar cell can be any one of a perovskite solar cell, a silicon / perovskite tandem solar cell, an organic / perovskite tandem solar cell, and other perovskite tandem solar cells, and its structure can also be a regular structure solar cell or an inverted structure solar cell and any other configuration in the prior art. Exemplarily, the solar cell unit is a perovskite solar cell unit, which includes: a bottom electrode, a hole transport layer, a perovskite light absorption layer, an electron transport layer and a top electrode stacked in sequence, wherein the material of the bottom electrode can be selected from any bottom electrode material suitable for perovskite solar cells, such as Ag, Au, Cu, C, Al, ITO, FTO, IWO, ICO, IZO, AZO, or other bottom electrode materials, which are not limited in this application; the material of the hole transport layer can be any hole transport layer material suitable for perovskite solar cells, such as PTAA, PEDOT:PSS, Spiro-OMeTAD, Poly-TPD, NiOX, CuSCN, CuI, NiO x , V2O5, 2PACz, MeO-4PACz, or other hole transport layer materials, which are not limited in the present application; the material of the perovskite light absorption layer can be prepared based on the perovskite pure phase microcrystalline material provided in the present application; the material of the electron transport layer can be any material of the electron transport layer material suitable for perovskite solar cells, such as at least one of PCBM, TiO2, ZnO, SnO2, H-PDI, F-PDI, C60, and ICBA, or other electron transport layer materials, which are not limited in the present application; the material of the top electrode can be any existing top electrode material suitable for perovskite solar cells, such as at least one of ITO, FTO, IWO, ICO, IZO, and AZO, or other top electrode materials, which are not limited in the present application.
[0116] Furthermore, the perovskite solar cell unit may also include other functional layers, such as an electron blocking layer and a hole blocking layer; illustratively, when the perovskite solar cell unit is provided with a hole blocking layer, the hole blocking layer is arranged between the electron transport layer and the top electrode, and the material of the hole blocking layer may be any existing hole blocking layer material suitable for perovskite solar cells, such as BCP, SnO2, or other hole blocking layer materials, or materials without a blocking layer, which are not limited in the present application.
[0117] The thickness of each layer structure in the solar cell unit can be adjusted as needed. Taking the perovskite solar cell unit as an example, for example, the thickness of the bottom electrode can be 80-150nm; the thickness of the hole transport layer can be 5-20nm; the thickness of the perovskite light absorption layer can be 600-800nm; the thickness of the electron transport layer can be 20-30nm; the thickness of the hole blocking layer can be 6-8nm and the thickness of the top electrode can be 80-300nm.
[0118] The above-mentioned pure phase perovskite microcrystalline material and its preparation method and application of the present application will be described below in conjunction with specific examples. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present application. If no specific technology or conditions are specified in the examples, they are carried out according to conventional technology or conditions in the art or according to the product instructions. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0119] Example 1
[0120] This embodiment provides a perovskite pure phase microcrystalline material, and the specific steps are as follows:
[0121] S1: Weigh 56.3g of lead iodide, 20.5g of formamidinium iodide (FAI), 11.4g of lead bromide, 8.7g of cesium iodide, 2.1g of lead chloride, and 0.5g of methylamine chloride (MACl), add them to 100ml of γ-butyrolactone, stir at room temperature until all are dissolved, and then filter the solution to obtain the filtrate as the precursor solution;
[0122] S2: Add the precursor solution to 1L of anisole under stirring at a rate of 0.05 ml / s. After the addition is complete, stop stirring and let stand for 1 min to generate a precipitate of alternating black and reddish brown.
[0123] S3: The precipitate was washed with anisole, mixed with 500 ml of anisole, and heated in an oil bath at 140° C. for 30 min until the precipitate turned pure black;
[0124] S4: After cooling to room temperature, the precipitate is washed with ethyl acetate for 2-3 times until the upper clear liquid is colorless, and then the precipitate is taken out and vacuum dried for 24 hours to obtain pure black α-phase wide band gap perovskite microcrystals with a band gap of 1.67-1.68 eV, hereinafter referred to as product A. The yield is calculated to be 91% after weighing.
[0125] Example 2
[0126] S1: Weigh 14.9g of lead bromide, 54.7g of lead iodide, 22.7g of FAI, and 7g of cesium iodide, add them into 100ml of δ-valerolactone, heat and stir at 100℃ until all dissolved, then filter the solution to obtain the filtrate as the precursor solution;
[0127] S2: Add the precursor solution to 1L of stirring o-xylene at a rate of 0.08ml / s. After the addition is complete, stop stirring and let stand for 3min to generate a gray-black precipitate.
[0128] S3: The precipitate was washed with o-xylene and heated in 500 ml o-xylene in an oil bath at 140°C for 60 min until the precipitate completely turned into pure black;
[0129] S4: After cooling to room temperature, the precipitate is washed with ether for 2-3 times until the upper clear liquid is colorless, and then the precipitate is taken out and vacuum dried for 24 hours to obtain pure black α-phase wide bandgap perovskite microcrystals with a band gap of 1.64 eV, hereinafter referred to as product B. The yield is calculated to be 90% after weighing.
[0130] Example 3
[0131] S1: Weigh 23.1g of lead bromide, 48.4g of lead iodide, 23.9g of FAI, and 7.4g of cesium iodide, add them into 100ml of a 1:1 mixed solution of ε-caprolactone and propylene carbonate, stir at 50°C until all dissolved, and then filter the solution to obtain the filtrate as the precursor solution;
[0132] S2: Add the precursor solution to 1L of anisole that is being stirred at a rate of 0.03ml / s. After the addition is complete, stop stirring and let stand for 1min to generate a gray-black precipitate.
[0133] S3: The precipitate was washed with anisole, mixed with 500 ml of anisole, transferred to a wide-mouth bottle, and heated in an oil bath at 140°C for 120 min until the precipitate completely turned pure black;
[0134] S4: After cooling to room temperature, the precipitate is washed with methyl acetate 2-3 times until the upper clear liquid is colorless, and then the precipitate is taken out and vacuum dried for 24 hours to obtain pure black α-phase wide bandgap perovskite microcrystals with a band gap of 1.70 eV, hereinafter referred to as product C. The yield is calculated to be 92% after weighing.
[0135] Example 4
[0136] S1: Weigh 17.2g FAI and 46.1g lead iodide and add them into 100ml ethylene glycol methyl ether, stir until they are completely dissolved, and then filter the solution to obtain the filtrate as the precursor solution;
[0137] S2: Add the precursor solution to 1L of anisole that is being stirred at a rate of 0.1ml / s. After the addition is complete, stop stirring and let stand for 2 minutes to generate a yellow precipitate.
[0138] S3: The precipitate was washed with anisole, mixed with 500 ml of anisole, and heated in an oil bath at 145°C for 60 min until the precipitate completely turned pure black;
[0139] S4: After cooling to room temperature, the precipitate was washed with ether for 2-3 times until the upper clear liquid was colorless, and then the precipitate was taken out and vacuum dried for 5 hours to obtain pure black narrow bandgap perovskite microcrystals with a bandgap of 1.5 eV, hereinafter referred to as product D. The yield was calculated to be 92% after weighing.
[0140] Example 5
[0141] S1: Weigh 15.9g MAI and 46.1g lead iodide and add them to 100ml γ-butyrolactone, stir until they are completely dissolved, and then filter the solution to obtain the filtrate as the precursor solution;
[0142] S2: Add the precursor solution to 1L of anisole that is being stirred at a rate of 0.15ml / s. After the addition is complete, stop stirring and let stand for 1min to generate a black precipitate.
[0143] S3: The precipitate was washed with anisole, mixed with 500 ml of anisole, and heated in an oil bath at 130°C for 20 min until the precipitate completely turned pure black;
[0144] S4: After cooling to room temperature, the precipitate was washed with methyl acetate for 2-3 times until the upper clear liquid was colorless, and then the precipitate was taken out and vacuum dried for 5 hours to obtain pure black narrow bandgap perovskite microcrystals with a bandgap of 1.55 eV, hereinafter referred to as product E. The yield was calculated to be 89% after weighing.
[0145] Comparative Example 1
[0146] Compared with Example 1, the good solvent A in this comparative example is DMF (which can dissolve the single component of the perovskite raw material in Example 1), and the remaining steps are the same as Example 1 to obtain a comparative product A. The calculated yield after weighing is 90%, but there are a large number of impurity peaks in the XRD spectrum, and the color is gray-black.
[0147] Comparative Example 2
[0148] Compared with Example 1, the good solvent A in this comparative example is γ-valerolactone (insufficient solubility for the perovskite raw material in Example 1), which cannot be completely dissolved during the preparation of the precursor solution, and there is a white precipitate. After filtration, the remaining steps are the same as in Example 1 to obtain a comparative product B. The calculated yield after weighing is 83%, but the band gap of the perovskite microcrystal becomes 1.63 eV, which is inconsistent with the experimental requirements and theoretical results.
[0149] Comparative Example 3
[0150] Compared with Example 1, in S2 in this comparative example, the addition rate of the precursor solution is 0.3 mL / s, and the remaining steps are the same as in Example 1. Flocculent agglomerates are formed during the precipitation of perovskite microcrystals, and finally a comparative product C is obtained. The calculated yield after weighing is 89%. The XRD spectrum shows the presence of residual intermediate phases, and the SEM shows that the grain size is uneven and the agglomeration phenomenon is serious. The single grain is ~1 μm and the agglomeration diameter is about 30 μm.
[0151] Comparative Example 4
[0152] Compared with Example 1, in S3 in this comparative example, the oil bath temperature of the antisolvent B is 150°C, and the remaining steps are the same as in Example 1, to obtain a comparative product D, the yield of which is calculated to be 88% after weighing, and a high-intensity lead iodide diffraction peak exists near 12.7° in the product XRD spectrum, indicating that the product is impure.
[0153] Comparative Example 5
[0154] Compared with Example 1, in S3 in this comparative example, the oil bath temperature of the antisolvent B is 120°C, and the remaining steps are the same as in Example 1, to obtain a comparative product E, the yield of which is 94% after weighing. There is a residual intermediate phase diffraction peak near 25-30° in the product XRD spectrum, and the SEM image shows that in addition to cubic block perovskite crystals, there are a small amount of rod-shaped crystals, and the product is impure.
[0155] Comparative Example 6
[0156] Compared with Example 1, step S3 is omitted in this comparative example, and the remaining steps are the same as in Example 1, to obtain a comparative product F. The yield calculated after weighing is 93%, the product is gray-black, and there is a high-intensity diffraction peak of the residual intermediate phase near 25 to 30° in the product XRD spectrum. The SEM image shows that in addition to cubic block perovskite microcrystals, there are a large number of rod-shaped crystals, and the product is impure.
[0157] Comparative Example 7
[0158] Compared with Example 1, the good solvent A in this comparative example is DMSO, the anti-solvent B is o-xylene, and the remaining steps are the same as those in Example 1. No crystals can be precipitated in the S2 stage.
[0159] In order to further study the beneficial effects of the preparation method of the pure phase perovskite microcrystalline material provided in the present application, the inventors also tested the X-ray diffraction (XRD) patterns and scanning electron microscope (SEM) characterization patterns of the products obtained in the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 6. The characterization results are as follows: Figure 1 to Figure 22 shown.
[0160] As can be seen from the figure, the products obtained in Examples 1-5 are free of impurities and have regular grains. However, if the synthesis is not performed according to the various parameters provided in this patent, the products obtained in Comparative Examples 1-6 have various problems such as residual intermediate phases, agglomeration of microcrystals, and residual lead iodide of the raw material.
[0161] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a pure phase perovskite microcrystalline material, characterized in that: include: Providing raw materials for forming perovskite, including a cationic compound for providing cations and an anionic compound for providing anions; Dissolving the raw material using good solvent A to form a precursor solution; Using antisolvent B to precipitate perovskite microcrystals; Using antisolvent B to phase-transform the perovskite microcrystals; Using anti-solvent C to wash the perovskite microcrystals to obtain pure phase perovskite microcrystal materials; The good solvent A has a solubility of not less than 0.4 mol / L for the whole raw material of the perovskite, and the good solvent A has a solubility of not more than 0.1 mol / L for some or all components in the raw material.
2. The method for preparing the pure phase perovskite microcrystalline material according to claim 1, characterized in that: The proton number of the good solvent A is not higher than 20.
3. The method for preparing the pure phase perovskite microcrystalline material according to claim 1, characterized in that: The good solvent A is a polar solvent, and is selected from at least one of ether solvents, lactone solvents, and organic acid ester solvents.
4. The method for preparing the pure phase perovskite microcrystalline material according to claim 3, characterized in that: The good solvent A is selected from at least one of ethylene glycol methyl ether, γ-butyrolactone, δ-valerolactone, ε-caprolactone, propylene carbonate and diethyl succinate.
5. The method for preparing the pure phase perovskite microcrystalline material according to claim 1, characterized in that: Any two of the good solvent A, the anti-solvent B and the anti-solvent C can be miscible in any proportion.
6. The method for preparing the pure phase perovskite microcrystalline material according to claim 5, characterized in that: The anti-solvent B has a solubility of no more than 0.1 mol / L for each component in the raw material; the anti-solvent B has a solubility of no more than 0.1 mol / L for the perovskite microcrystals; and / or The solubility of the anti-solvent C for each component in the raw material is no higher than 0.1 mol / L; the solubility of the anti-solvent C for the perovskite microcrystals is no higher than 0.1 mol / L.
7. The method for preparing the pure phase perovskite microcrystalline material according to claim 1, characterized in that: The boiling point of the anti-solvent B is 140-165° C.; and / or The boiling point of the anti-solvent C is 40-80°C.
8. The method for preparing a pure phase perovskite microcrystalline material according to claim 1, characterized in that: The anti-solvent B is a non-polar or low-polar solvent selected from benzene solvents, ether solvents, and ester solvents with no less than 4 carbon atoms on the carbon chain.
9. The method for preparing a pure phase perovskite microcrystalline material according to claim 1, characterized in that: The anti-solvent B is selected from at least one of anisole, o-xylene and butyl propionate; and / or The anti-solvent C is selected from at least one of diethyl ether, toluene, cyclopentane, ethyl acetate and methyl acetate.
10. The method for preparing a pure phase perovskite microcrystalline material according to claim 1, characterized in that: In the precursor solution, the overall concentration of the perovskite is not less than 0.4 mol / L.
11. The method for preparing a pure phase perovskite microcrystalline material according to claim 1, characterized in that: The volume ratio of the good solvent A, the anti-solvent B and the anti-solvent C is 1:(3-20):(1-3).
12. The method for preparing a pure phase perovskite microcrystalline material according to claim 1, characterized in that: Using anti-solvent B to precipitate perovskite microcrystals, comprising: Slowly drop the precursor solution into the anti-solvent B, stir, and let stand to obtain a precipitate; The adding speed of the precursor solution is 0.03-0.2 mL / s; and the stirring speed is 500-2000 rad / min.
13. The method for preparing a pure phase perovskite microcrystalline material according to claim 1, characterized in that: The perovskite microcrystals are phase-changed by using an anti-solvent B, comprising: The perovskite microcrystals and anti-solvent B are mixed, heated at a temperature not higher than the boiling point of the anti-solvent B for 30 to 180 minutes, cooled, and allowed to stand to obtain a pure phase perovskite microcrystal precipitate.
14. The method for preparing a pure phase perovskite microcrystalline material according to claim 1, characterized in that: The perovskite microcrystals are washed with anti-solvent C to obtain a pure phase perovskite microcrystal material, including: The pure phase perovskite microcrystals that have undergone phase change are precipitated, washed 3-5 times with anti-solvent C, filtered, and vacuum dried to obtain pure phase perovskite microcrystals.
15. The method for preparing a pure phase perovskite microcrystalline material according to claim 1, characterized in that: The cationic compound is selected from the group consisting of + , Rb + , K + 、Na + At least one compound selected from the group consisting of + 、MA + DMA + , MDA + At least one compound of The anionic compound is selected from the group consisting of - Br - , Cl - HCOO - 、SCN - 、BF4 - PF6 - At least one compound.
16. The method for preparing a pure phase perovskite microcrystalline material according to claim 1, characterized in that: The raw materials include lead iodide, formamidine iodine, lead bromide, cesium iodide, lead chloride, and methylamine chloride; The good solvent A has a solubility of no more than 0.1 mol / L for the lead iodide, lead bromide, cesium iodide, lead chloride and methylamine chloride.
17. A perovskite pure phase microcrystalline material, characterized in that: The perovskite pure phase microcrystalline material is prepared by the preparation method according to any one of claims 1 to 16.
18. The perovskite pure phase microcrystalline material according to claim 17, characterized in that: The particle size of the perovskite pure phase microcrystalline material is 0.5 to 2 μm.
19. Application of the pure phase perovskite microcrystalline material prepared by the preparation method according to any one of claims 1 to 16 or the pure phase perovskite microcrystalline material according to any one of claims 17 to 18 in the fields of X-ray detection, solar cells, and photoelectric detection.
